Flexible pressure sensors using highly-oriented and free-standing carbon nanotube sheets. (November 2018) - Chun, Sungwoo; Son, Wonkyeong; Choi, Changsoon
Abstract: Carbon allotropes are strong candidates for pressure sensing materials in flexible electronics due to their extraordinary mechanical and electrical properties. However, the complexity of the conventional transfer process for these allotropes, the success of which is strongly dependent on the surface conditions of the substrates, limits their feasibility for use as pressure sensors. Thus, we propose a method to create flexible pressure sensors using highly-oriented and free-standing hydrophobic carbon nanotube (CNT) sheets. When drawn from a sidewall of a carbon nanotube forest, these sheets only require a single transfer process without any chemical treatment, thereby facilitating a simple, cost-effective transfer method. The resulting sensors exhibit high sensitivity and fast response characteristics for both statically and dynamically applied pressures. In addition, the highly-oriented structure of these CNT sheets results in distinctive response characteristics for bi-axially applied bending strains. It was also confirmed that the sheets can be easily transferred onto any substrate, including those with rough surfaces, due to the naturally formed free-standing structure. In this work, we present the intact transfer of a CNT sheet onto a micro-patterned substrate representing a rough surface and demonstrate the accompanying typical piezoresistive responses of the resulting pressure sensor. Graphical abstract: Image 1